Regulatorni vidik predpisovanja kanabinoidov - Čufar, Andreja (Farmacevtski vestnik, 2016)
Cannabis is one of the most popular drugs on the one side and a medicinal product on the other. It contains about 70 different psychoactive compounds, whose function is still not fully undrestood. International legal framework in the field of illicit drugs is defined by three United Nations Conventions, namely the Single Convention on Narcotic Drugs, 1961, amended in 1972, the Convention on Psychotropic Substances, 1971 and the Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances, 1988. The European Union Member States classify drugs and precursors in accordance with these three conventions. Within the framework of their national laws, the Member States regulate the scope of illicit drugs in different ways in detail, thereby enabling their medical use and preventing their potential abuse at the same time. In Slovenia, recently amended Regulation on the classification of illicit drugs enables the availability of medicines with isolated or synthesized 9 - tetrahydrocannabinol, nabilone, and medicines with extracts from cannabis, including tinctures, standardized to delta-9-tetrahydrocannabinol. Based on this regulation pharmacists can also compound magistral and galenic medicines from those substances.
Keywords: Konoplja; konvencija Združenih narodov; medicinska konoplja; predpisovanje zdravil; tetrahidrokanabinol; uredba o prepovedanih drogah; Zakonodaja